CP-031 Clinical use of lenalidomide for the treatment of multiple myeloma. (14th February 2016) - Monje, B; Escudero-Vilaplana, V; Revuelta, JL; Garcia-Gonzalez, X; Ortega-Navarro, C; Tovar-Pozo, M; Sanjurjo-Saez, M
Abstract : Background: In April 2009, lenalidomide was included in the hospital formulary for the treatment of multiple myeloma (MM) in patients who had received at least one previous therapy. The recommended starting dose (25 mg of lenalidomide) should be adjusted according to clinical and laboratory findings. Purpose: Our objective was to assess the prescription profile of lenalidomide in a tertiary hospital and compliance with the hospital formulary criteria. Material and methods: A retrospective observational study was performed to analyse the clinical and pharmacotherapeutic characteristics of patients treated with lenalidomide. Inclusion criteria: MM patients treated with lenalidomide from January 2015 to August 2015. Recorded variables were: age, gender, diagnosis, prior chemotherapy, bone marrow transplant, thromboprophylaxis treatment, basal paraprotein level, glomerular filtration rate (GFR), start date of treatment, starting dose of lenalidomide and reasons for dose adjustment. Results: 52 patients (53.8% male) with a median age (p25, p75) of 71.5 years (61.2, 79.0) were included. Median time since diagnosis was 3.1 years (1.4, 7.0). All patients received prior chemotherapy and 24 patients (46.1%) underwent bone marrow transplant. 43 patients (82.7%) received thromboprophylaxis treatment. Lenalidomide was prescribed as a second line treatment in 20 patients (38.6%), as a third line in 20 patients (38.6%) and as a fourth or more line in 12 patients (22.8%). Patients showed a mean basal paraprotein level of 1.1 g/dL (SD 1.3). GFR was diminished in 15 patients (28.8%) at the beginning of treatment: 10 patients had moderate renal impairment (30–50 mL/min) and 5 patients had end stage renal disease (<30 mL/min). 26 patients (50.0%) received 25 mg of lenalidomide. Due to diminished renal function, 10 patients (19.2%) started with a dose of 10 mg and 5 patients (9.6%) with 5 mg. 15 mg was the starting dose in 11 patients (21.2%) due to neutropenia and thrombocytopenia. Conclusion: Lenalidomide was primarily used as a second or third line treatment in clinical practice, meeting the criteria of our hospital formulary. Only 50.0% of patients started their treatment with the standard dose. This highlights the importance of focusing on clinical characteristics, such as renal function or haematological disorders, for the dose adjustment of lenalidomide. No conflict of interest.